Analysis of the contributions of National Parks and Biological Reserves to the socioeconomic development of Costa Rica, 2009. - Moreno Díaz, Mary Luz (2010)
Costa Rica has a quarter of its territory protected, of which 12.7% corresponds to the category of national parks and biological reserves. These protected areas-a total of 28 national parks and biological reserves in- provide the country benefits not only ecological but also economic, social and institutional ones, which are reflected in activities such as tourism, protection of water resources for hydroelectric energy, environmental services, and scientific research, among others. In 2002, was found that the contributions generated by the existence of national parks and biological reserves to socio-economic development in Costa Rica was ¢ 334 128 million (US$832 million). We also obtained the datum for the national parks of Chirripó (¢243 million, US$618 million), Cahuita (¢1.977 million, US$4.9 million) and Poas Volcano (¢9.345 million, US$23.4 million) (Furst et al, 2005). With the urge of updating the data obtained for 2002 was proposed the project Systematization and Analysis of the Contributions of National Parks and Biological Reserves to the Economic and Social Development in Costa Rica, Benin and Bután1 , which also sought to replicate the methodology in two other countries and work with other case studies in Costa Rica, as well as to propose policy recommendations to support to decision makers in the management of national parks and biological reserves in the three countries. The information found at the national level and empirically aggregated on the main activities or contributions identified in this study shows that economic activities that were benefited from the existence of the PNRB for 2009 were: (1) tourism aimed primarily at nature with its related services, (2) generation of electricity through the usage of water coming from the PNRB for hydroelectric projects, (3) generation of employment and salaries, (4) incomes from MINAE in the quality of tickets collected, (5) conservation of protected wildlife areas from MINAE-SINAC in the form of fixed costs and investments in the administration and maintenance of the PNRB (6) purchase of lands for the expansion of existing PNRB or the establishment of new ones, (7) payment for environmental services (PSA) aimed at protected areas for their conservation and maintenance, and finally (8), research on biodiversity and, corresponding to this, generation of profits in the quality of bioprospection and basic research. In an effort to interpret these contributions in monetary terms, the search, systematization and analysis of primary and secondary information allows making an estimate of the contributions of PNRB for 2009. This year the total sum of the approximate contributions of the activities mentioned in the previous paragraph was ¢778.148 million colones or $1.357 million dollars (in prices of 2009). This amount represents a contribution to the economic development of undeniable importance, but it should be seen as the lower limit of a much higher amount, in case of having a more solid statistical basis, and include the actual amount of the environmental services attributable to PNRB. Always considering the restriction noted, the estimated total of contributions to the national economy in the quality of income generation and investment attributable to PNRB, is about 5 percent of GDP in Costa Rica in 2009 (own calculation based on the National Accounts of BCCR for 2009). In the framework of this Project, was also worked with three case studies, with the following results: Corcovado National Park-Caño Island Biological Reserve in 2008 ₡48.197 million colones or $91.590 thousand dollars (Otoya, M. et al 2010); Rincón de la Vieja National Park in 2009 ₡12.770 million colones or $23.010 thousand dollars (Salas, F. et al 2010); and Palo Verde National Park in 2009 ₡1.106 million colones or $1.936 thousand dollars (Moreno, M. et al 2010).